Subscriber retention management: SRM framework and future research agenda - Muratčehajić, D.; Loureiro, S. M. C. (Journal of Services Marketing, 2024)
Purpose This article aims to systematically review the fragmented but increasingly relevant research field of customer retention management in subscription scenarios, proposing the subscriber retention management framework for retention management in subscription settings and directing future research. Design/methodology/approach The authors systematically reviewed 1,295 articles to offer a comprehensive, unbiased overview on customer retention management in subscription-based services. From 122 selected articles, the authors conducted a descriptive analysis, conceptualized key insights into a novel framework and recognized research gaps. Findings Among 122 articles, 111 focus on private customers across various service sectors, while lacking reflection on new digital industries, reactive retention and the corporate context. The conceptualization of results merges existing insights into seven dimensions, encompassing strategic and tactical aspects and the interplay of controllable and uncontrollable factors. The authors also outline 12 emerging research directions. Research limitations/implications Given the extensive body of literature, the authors were unable to delve into detailed explanations. The findings are limited to management science research sourced from Scopus, adhering to a rigorous filtering process. Sub-domains, such as reactive or business-to-business retention management, remain somewhat provisional due to little results. Practical implications A sustainable subscriber retention strategy hinges on: (1) integrating retention into business strategy, (2) adjusting acquisition and retention tactics to specific markets and (3) using a consistent retention marketing mix considering affective, calculative and habitual commitment factors. Originality/value The authors contribute with a first systematic review of subscription-specific retention management in a rapidly growing area. This results in a novel framework that broadens the understanding of subscriber retention and identifies research gaps.